Supply Chain Management and Network Distribution of Safal Market - Muttalageri, Mahadevappa; Chandrashekar, H. M. (Prabandhan: Indian Journal of Management, 2009)
Supply Chain Management consists of all parties involved directly or indirectly in fulfilling a customer request. The supply chain not only includes the producers and suppliers but also transporters, warehouses, retailers, and customer themselves within each organization such as producer, the supply chain includes all function involved in receiving and filling consumer request. Improving the post harvest management means an overall improvement in the per unit productivity. In last one decade various marketing models have been initiated, Mother Dairy cooperatives in fresh fruits and vegetables under the name of SAFAL, further their alternative whole sale market-SAFAL Market. The traditional Indian markets have a non-existent infrastructure of packing, grading, sorting and cold storages. The commission agents and traders dominate the supply chain and are the major price setters, thus most of the times farmers are dependent on them for credit. Farmers are not aware of the price setting mechanisms as the system is not transparent and thus don't have any incentive to produce efficiently. The National Dairy Development Board (NDDB) has started the Fruit and Vegetable Unit of SAFAL at Delhi, which is one of the first fruit and vegetable retail chains set up as a part of the Mother Dairy Foods Processing Ltd. The retail unit provided a direct link between fruit and vegetable growers and consumers. The other initiative was a fruit processing Plant of SAFAL at Mumbai, a 100 per cent export-oriented unit, which capitalizes NDDB's food processing strength. NDDB has set up an alternate system of wholesale markets in Bangalore as a pilot project. The initiative is named as SAFAL Market and is initiated to fine-tune horticultural growth in India, by a shift in their earlier retail chain model to a wholesale market concept.This paper addresses the Supply Chain Management as it concerns with 'integration' of firms in the face of coordinating materials and information flows within a procurement-production-distribution network in order to attain the Safal Market goals with special reference to fruits and vegetables.